7(x-7)=-4-16

Simple and best practice solution for 7(x-7)=-4-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-7)=-4-16 equation:


Simplifying
7(x + -7) = -4 + -16

Reorder the terms:
7(-7 + x) = -4 + -16
(-7 * 7 + x * 7) = -4 + -16
(-49 + 7x) = -4 + -16

Combine like terms: -4 + -16 = -20
-49 + 7x = -20

Solving
-49 + 7x = -20

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '49' to each side of the equation.
-49 + 49 + 7x = -20 + 49

Combine like terms: -49 + 49 = 0
0 + 7x = -20 + 49
7x = -20 + 49

Combine like terms: -20 + 49 = 29
7x = 29

Divide each side by '7'.
x = 4.142857143

Simplifying
x = 4.142857143

See similar equations:

| -6.3m+2.7m= | | 0.75x+37-2.75=3(4+x) | | 5x-4=8x+12 | | 0.6x=0.5 | | 13x-8=43 | | 6(3x-1)=5 | | 3p-9=30 | | 14-3s=5 | | 4x-x^4=-4 | | 4x+-3=2x+4 | | 4x-4/5=11/5 | | 5q+4(-7+5q)=1-g | | 5x-8=7x-24 | | 5(x+2)=5x+11 | | 14+4k=-2+2k | | y=2x+-7 | | N/5-6=18 | | 1-x=2/5 | | -4n/4=22/3 | | 3x+6x-9=0 | | 4(2x-4)=8x+-16 | | F(x)=13x+3 | | 4=z/9(4y-2) | | 3s-4=5 | | 2(x-1)(4x+3)=0 | | 2/3x-12=2 | | 4x+80=5x+80 | | 5(x+2)-8x=19 | | x=3x+-2 | | 7q-48+3q+6=180 | | -4(b+8)=-25-5b | | 16x^2-96x+48=0 |

Equations solver categories